Social Comparison and related psychosocial variables: a review of cancer and chronic pain - Terol, Maria del Carmen; Neipp, María del Carmen; Lledó-Boyer, Ana; Pons, Nieves; Bernabé, Miguel (Anales de Psicología / Annals of Psychology, 2012)
The concept of social comparison has aroused great interest in the research that evaluated the health state. The aims of this paper are to review the construct of social comparison in cancer patients and chronic pain and to study the relationship of social comparison with other psychosocial variables and adaptive outcomes. It was consulted databases Medline and PsycInfo and obtained a total of 69 report for cancer patients and 20 for patients with chronic disease. To the construct review, we selected a total of 22 empirical studies in cancer patients and 9 studies to chronic disease. The results of the review showed that most studies have used ad hoc developed tool. This is an obstacle to results replication. Moreover, not all the papers consulted include the two dimensions of social comparison (orientation and interpretation) to properly analyze the influence of social comparison. The theoretical implications are discussed at paper.